A distributed optimal power management system for microgrids with plug&play capabilities. Issue 1 (21st January 2021) - Hosseinzadeh, Mehdi; Schenato, Luca; Garone, Emanuele
Abstract: In this article we consider the problem of managing the power flow among different components of a microgrid while ensuring that the demands of all loads are satisfied. In order to address this problem, we propose a distributed scheme where only one sensor (for each subgrid in the microgrid) broadcasts a single scalar variable though a wireless communication network (e.g., WiFi, ZigBee, cellular communication network). More precisely, in the proposed scheme each generation/storage subsystem is able to adjust its operating set‐point only making use of the feedback from the sensors. This architecture provides the system with plug&play capabilities. Interestingly enough, the proposed scheme provides the optimal power flow for the whole microgrid without any information on the demanded load. In this article we apply the proposed approach to hybrid ac/dc microgrids; however, the scheme is general and can be applied to any type of microgrid. The effectiveness of the proposed scheme is evaluated through extensive simulations and compared with a centralized optimal strategy. Abstract : This paper develops a distributed power management system to optimize power flow among different components of a microgrid, while ensuring that the demands of all loads are satisfied. The developed system has plug&play capabilities, where each subsystem is able to adjust its operating setpoint only making use of the feedback from power sensors.